Carcinoma of maxillary sinus mimicking a deep fungal infection- a rare case report - Pinto, Melisha Rolita (Journal of Orofacial Research, 2020)
Carcinoma of maxillary sinus is an uncommon tumor of head and neck region. The clinical presentation depends on the involvement of sinus wall. The nonspecific nature of the presentation often leads to delayed diagnosis which results in poor prognosis and survival rate. Here we report a case of carcinoma of left maxillary sinus with an intraoral swelling and extraoral swelling with ulcer at infraorbital region mimicking a deep fungal infection. Because of extensive involvement, the patient was subjected to chemoradiation.